Coaxial CoMoO4 nanowire arrays with chemically integrated conductive coating for high-performance flexible all-solid-state asymmetric supercapacitors. Issue 37 (10th August 2015) - Chen, Yaping; Liu, Borui; Liu, Qi; Wang, Jun; Li, Zhanshuang; Jing, Xiaoyan; Liu, Lianhe
Abstract : CoMoO4 nanowire arrays on carbon cloth (CC) improve the supercapacitor performance. Meanwhile, a flexible all-solid-state asymmetric supercapacitor (ASC) device demonstrates highly stable cyclic performance with outstanding robust flexibility. Abstract : Flexible all-solid-state supercapacitors have offered promising applications as novel energy storage devices based on their merits, such as small size, low cost, light weight and high wearability for high-performance portable electronics. However, one major challenge to make flexible all-solid-state supercapacitors depends on the improvement of electrode materials with higher electrical conductivity properties and longer cycling stability. In this article, we put forward a simple strategy to in situ synthesize 1D CoMoO4 nanowires (NWs), using highly conductive CC and an electrically conductive PPy wrapping layer on CoMoO4 NW arrays for high performance electrode materials. The results show that the CoMoO4 /PPy hybrid NW electrode exhibits a high areal specific capacitance of ca. 1.34 F cm −2 at a current density of 2 mA cm −2, which is remarkably better than the corresponding values for a pure CoMoO4 NW electrode of 0.7 F cm −2 . An excellent cycling performance of nanocomposites of up to 95.2% ( ca . 1.12 F cm −2 ) is achieved after 2000 cycles compared to pristine CoMoO4 NWs. In addition, we fabricate flexible all-solid-state ASC which can be cycled reversibly in the voltage range of 0–1.7 V, and exhibits a maximum energy density of 104.7 W h kg −1 (3.522 mW h cm −3 ), demonstrating great potential for practical applications in flexible energy storage electronics.